Meningkatkan Kemampuan Berpidato Peserta didik Sekolah Dasar Melalui Pemanfaatan Media yang Inovatif dan Terintegrasi - Fadilah Nur Hanifah; Amelia Hana Salsabila; Dian Kartika Prabaningrum; Yulinda Sari; Bayu Purba Sakti (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The ability to speak is an essential communication skill that needs to be developed from an early age. In elementary school students, mastery of this ability is often hampered by psychological factors such as shyness, lack of self-confidence, or social anxiety, as well as cognitive constraints in composing and organizing ideas coherently. This article elaborates on the strategic role of various innovative media in improving speech communication in elementary school students. The discussion focuses on the integration of visual, audio-visual, and interactive media that can create a fun, inclusive, and highly effective learning environment. The elaboration includes an in-depth review of basic communication theories and the developmental characteristics of elementary school students, as well as detailed identification and description of relevant media types, complete with practical guidelines for implementing and evaluating their use in the classroom. The research method used is a systematic literature study from various leading academic sources. The results of the discussion show that the strategic use of media can facilitate the process of learning to speak, reduce anxiety, and increase student motivation. It is hoped that this article will provide comprehensive insights and practical guidelines for educators, parents, and educational policy makers in selecting, designing, and utilizing the right media to encourage elementary school students to become confident, articulate, and persuasive speakers.